Prognosis of stroke in a patient with SARS-CoV-2 and coronary artery bypass graft surgery - Menegassi, Felipe Gustavo Morais; Resende, Valéria Cardoso Pinto; de Moura, Flávio José Dutra (Seven Editora, 2023)
Objective: To report a case of a patient with ischemic stroke, previous coronary artery bypass graft surgery (CABG), and cardiovascular and endocrine-metabolic comorbidities associated with complications from SARS-CoV-2. Case details: A 75-year-old patient was admitted to a referral hospital in Brasilia/Federal District in June 2020 due to sudden loss of consciousness, hemiparesis in the right dimidium, and aphasia with conjugated ocular deviation for 1 hour. He has coronary artery disease with coronary artery bypass graft surgery 3 years ago, arterial hypertension, chronic kidney disease stage IV by the Chronic Kidney Disease Epidemiology Collaboration, hypothyroidism, metabolic syndrome, and obstructive sleep apnea syndrome. During hospitalization, RT-PCR was performed with the detection of the RNA of SARS-CoV-2 and chest CT showing opacities with ground-glass attenuation and inflammatory bronchopathy. Final considerations: In the presence of coronavirus, ischemic stroke occurs in the most severe cases of the disease, due to the neurotropism of the virus and the complications of the patient with cardiovascular comorbidities. Coronary artery bypass graft surgery represents a worse prognosis factor when in the immediate postoperative period in these patients with a high mortality rate. However, in the present case, the patient with a history of CABG had a favorable clinical outcome. DOI:https://doi.org/10.56238/emerrelcovid19-019